Direct conversion of shrimp shells to O-acylated chitin with antibacterial and anti-tumor effects by natural deep eutectic solvents. Issue 1 (31st October 2018) - Feng, Mi; Lu, Xingmei; Zhang, Jie; Li, Yi; Shi, Chunyan; Lu, Lingling; Zhang, Suojiang
Abstract : O -Acylated chitin was obtained directly from shrimp shells using ChCl/RCOOH (NADESs), which exhibited good antibacterial and anti-tumor effects. Abstract : To obtain O -acylated chitin from shrimp shells directly, the used solvent should have multiple functions to remove calcium carbonate, protein, and acylated chitin. Herein, we use the acidic natural deep eutectic solvents (NADESs) with the ability to release H + and various hydrogen bonding sites to achieve the above goal. The involved NADESs with three abilities of decalcification, deproteinization and acylation replaced acids, alkalis, catalysts, and acylation reagents in the conventional method. The experimental results revealed that the components of the NADESs, experiment temperature and time played key roles in the purity and degree of substitution (DS) of O -acylated chitin. Meanwhile, the ratio of shrimp shells to NADESs and a small amount of water had little effect on the preparation of O -acylated chitin. With the optimal NADES (choline chloride/dl -malic acid 1 : 2, ChCl 1–dl Mal 2) treatment under the optimal conditions, the purity of O -malate chitin reached 98.6% with a DS of 0.46, exhibiting antibacterial and anti-tumor effects. The experimental results showed that the removal of calcium carbonate and protein and acylation of chitin were carried out simultaneously. Mechanistic exploration using spectroscopy and experiments confirmed that H + release from ChCl 1–dl Mal 2 was the main reason for the removal of calcium carbonate and initiation acylation reaction. The protein was degraded to amino acids because of the acidity of ChCl 1–dl Mal 2 and dissolved in the NADES due to hydrogen bonding formation with ChCl 1–dl Mal 2.